ABOUT LINGUISTIC FACTORS OF THE PENETRATION OF LACUNAE FROM ONE LANGUAGE INTO OTHERS - Dildarhan Urinbaevna Khashimova (The Conference Hub, 2026)
This article discusses how the art of communication has acquired global significance in our time, as it forms the basis for relationships, mutual understanding, and interaction between individuals, entire peoples, and states. In this regard, the realities of one language penetrate other languages: a) through historical, spiritual, cultural, social, and political contacts; b) through the dissemination of scientific and technical discoveries; c) through the artistic translation of literary works; d) through the use of lacunae in the vernacular by foreign writers and translators.
Keywords: language, culture, reality, lacuna, semanticization, clarity, interpretation, commentary, transcription, translation, ethnocultural studies, intercultural communication, national culture, comparison of phenomena, facts of Russian history and culture, passive minimum.